2006
DOI: 10.1029/2006gl026736
|View full text |Cite
|
Sign up to set email alerts
|

Planktivorous auklet Ptychoramphus aleuticus responses to ocean climate, 2005: Unusual atmospheric blocking?

Abstract: In spring‐summer 2005, anomalous atmospheric‐oceanographic coupling caused unprecedented reproductive failures and redistribution of a planktivorous marine bird in both central California (37°N) and southern British Columbia (50°N). At SE Farallon Island, CA, the birds abandoned the breeding colony en masse between 10–20 May, a unique behavioral response; for the first time in 35 years, reproductive success was zero. At Triangle Island, B.C., only 8% of the nesting pairs were successful, the worst year on reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 26 publications
2
139
0
Order By: Relevance
“…The ecological consequences of these changes are potentially severe. The low recruitment of the intertidal species reported here is consistent with lower-than-normal concentrations of zooplankton (17) in the northern CCLME. Reproductive failure of a planktivorous seabird, Cassin's auklet (Ptychoramphus aleuticus) in the CCLME during 2005 (17) is also a likely result of the chain of reductions at lower trophic levels in coastal food webs initiated by the reduced nutrients and phytoplankton at a critical time in the life history of coastal seabirds.…”
Section: Resultssupporting
confidence: 69%
“…The ecological consequences of these changes are potentially severe. The low recruitment of the intertidal species reported here is consistent with lower-than-normal concentrations of zooplankton (17) in the northern CCLME. Reproductive failure of a planktivorous seabird, Cassin's auklet (Ptychoramphus aleuticus) in the CCLME during 2005 (17) is also a likely result of the chain of reductions at lower trophic levels in coastal food webs initiated by the reduced nutrients and phytoplankton at a critical time in the life history of coastal seabirds.…”
Section: Resultssupporting
confidence: 69%
“…In addition, owing to the prevalence of changes in the timing of seasonal coastal warming, phenological changes driven by current and future warming are likely to increase 51 . This might be problematic because effects in one species often cascade across trophic webs 36,52 and thus single-species perturbations often have broader ecological implications. It is undeniable that a more detailed exploration of the relation between the different regional or seasonal warming regimes and the distinct biotic responses is required.…”
Section: Discussionmentioning
confidence: 99%
“…Temperatures on these coasts are largely dominated by decadal changes in circulation patterns such as the Pacific Decadal Oscillation and the El Niño/Southern Oscillation 33,34 , which frequently alternate between contrasting warm and cold phases. Large-scale temperature fluctuations are important drivers on the biogeographic patterns observed on the Eastern pacific coast 35 , and while several studies have reported population and poleward range shifts associated with episodes of abnormally high SST 36,37 , others show that during cold phases species distributions may be driven in equatorialwards 33 , or may not change at all 38 .…”
Section: Global Patternsmentioning
confidence: 99%
“…High dinoflagellate biomass during this period was not just a local phenomenon for the inshore region of the southern CCE. Dominant toxin-producing algal species in central California shifted from diatoms to dinoflagellates (Jester et al, 2009), and there were also reports of reduced zooplankton biomass, reduced seabird fecundity and altered marine mammal foraging in more northern waters (Peterson et al, 2006;Sydeman et al, 2006;Weise et al, 2006). Additionally, northern anchovy densities decreased significantly from 2005 to 2006 off the Oregon and Washington coast, and fatty acid biomarkers of northern anchovy, Pacific herring and whitebait smelt indicated that the food web in 2005 was mainly based on dinoflagellates, switching back to diatoms in 2006 (Litz, 2008;Litz et al, 2008).…”
Section: Community Compositionmentioning
confidence: 99%